1992
DOI: 10.1172/jci115559
|View full text |Cite
|
Sign up to set email alerts
|

Increased susceptibility of differentiated mononuclear phagocytes to productive infection with human immunodeficiency virus-1 (HIV-1).

Abstract: Differences in susceptibility to infection of most mononuclear phagocytes with HIV-1 are not known. We investigated the relative susceptibility of autologous freshly isolated blood monocytes (MN), MN cultured in vitro to allow differentiation (CM), and alveolar macrophages (AM) from healthy subjects to productive infection with HIV-1. Cells were infected with the macrophage tropic strain HIV-1jRFL and p24 gag antigen levels measured in supernatants by ELISA. Freshly isolated MN had negligible levels of p24 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
149
0
2

Year Published

1992
1992
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 211 publications
(159 citation statements)
references
References 32 publications
8
149
0
2
Order By: Relevance
“…Because HIV-1 DNA in BAL was found almost exclusively in the macrophage-enriched fraction, these findings raise the possibility that this V3 loop (12) and cellular localization ofviral RNA and DNA (10,27,28). These cells are much more susceptible to HIV-1 infection than are circulating monocytes and produce far higher levels of infectious virus after primary inoculation with macrophage tropic viral isolates (29). Once infection becomes established, the mechanisms allowing for the persistence of viral infection in tissue macrophages remain unresolved.…”
Section: Discussionmentioning
confidence: 93%
“…Because HIV-1 DNA in BAL was found almost exclusively in the macrophage-enriched fraction, these findings raise the possibility that this V3 loop (12) and cellular localization ofviral RNA and DNA (10,27,28). These cells are much more susceptible to HIV-1 infection than are circulating monocytes and produce far higher levels of infectious virus after primary inoculation with macrophage tropic viral isolates (29). Once infection becomes established, the mechanisms allowing for the persistence of viral infection in tissue macrophages remain unresolved.…”
Section: Discussionmentioning
confidence: 93%
“…It is well-known that monocytes are refractory to HIV infection in vitro and in vivo. [37][38][39][40][41] This refractory property to HIV infection could be because monocytes express high levels of intracellular innate anti-HIV factors, including miRNAs. 23 We were particularly interested in miRNA-28, miRNA-125b, miRNA-150, miRNA-223, and miR-382 because these miRNAs can target a highly conserved region of HIV, present in all HIV clades.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies indicate that circulating monocytes also serve as a viral reservoir in infected individuals (15)(16)(17)33). The infection of circulating monocytes in vivo is at odds with in vitro studies, where monocytes acquire the ability to support productive viral infection only after their differentiation to macrophages (2,4,5,19,20,23,25). While most studies have suggested that the viral replication cycle in monocytes is restricted at a point prior to establishment of the provirus, the exact point of restriction is a matter of debate.…”
mentioning
confidence: 99%